1, 3‐Regiospecific ethanolysis of soybean oil catalyzed by crosslinked porcine pancreas lipase aggregates. (7th May 2018) - Ramos, Margarita D.; Miranda, Letícia P.; Giordano, Raquel L. C.; Fernandez‐Lafuente, Roberto; Kopp, William; Tardioli, Paulo W.
Abstract : The preparation of crosslinked aggregates of pancreatic porcine lipase (PPL‐CLEA) was systematically studied, evaluating the influence of three precipitants and two crosslinking agents, as well as the use of soy protein as an alternative feeder protein on the catalytic properties and stability of the immobilized PPL. Standard CLEAs showed a global yield (CLEA' observed activity/offered total activity) of less than 4%, whereas with the addition of soy protein (PPL:soy protein mass ratio of 1:3) the global yield was approximately fivefold higher. The CLEA of PPL prepared with soy protein as feeder (PPL:soy protein mass ratio of 1:3) and glutaraldehyde as crosslinking reagent (10 μmol of aldehyde groups/mg of total protein) was more active mainly because of the reduced enzyme leaching in the washing step. This CLEA, named PPL‐SOY‐CLEA, had an immobilization yield around 60% and an expressed activity around 40%. In the ethanolysis of soybean oil, the PPL‐SOY‐CLEA yielded maximum fatty acid ethyl ester (FAEE) concentration around 12‐fold higher than that achieved using soluble PPL (34 h reaction at 30°C, 300 rpm stirring, soybean oil/ethanol molar ratio of 1:5) with an enzyme load around 2‐fold lower (very likely due to free enzyme inactivation). The operational stability of the PPL‐SOY‐CLEA in the ethanolysis of soybean oil in a vortex flow type reactor showed that FAEE yield was higher than 50% during ten reaction cycles of 24 h. This reactor configuration may be an attractive alternative to the conventional stirred reactors for biotransformations in industrial plants using carrier‐free biocatalysts. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:910–920, 2018